Optimalisasi Pemasaran Zakat di Indonesia: Wawasan Strategis dari Tinjauan Literatur yang Sistematis - Anton Priyo Nugroho; Lukman Hamdani; Atep Hendang Waluya (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Zakat serves as a vital instrument of Islamic philanthropy that enhances social welfare and fosters sustainable socioeconomic progress. Nevertheless, its vast potential in Indonesia remains underutilized. This study aims to provide a comprehensive understanding of zakat marketing to guide practitioners and policymakers in maximizing zakat contributions. Employing a Systematic Literature Review (SLR) approach, the research explores the strategic dimensions influencing zakat marketing effectiveness. The findings reveal four principal dimensions: technological innovation, demographic characteristics, zakat literacy and religiosity, and fundraising with financial security. Organizational strategies encompass digital content inclusiveness, Sharia-based marketing, zakat education, and collection mechanisms, while individual determinants include social media influence, campaign awareness, religiosity, and gender-related financial behavior. The study concludes that integrating digital tools and literacy-based strategies can significantly improve zakat collection and distribution. It also highlights the need for future research to expand global perspectives, adopt diverse methodologies, and examine external socio-economic factors affecting zakat participation.